2020
DOI: 10.1007/s00330-020-07401-8
|View full text |Cite|
|
Sign up to set email alerts
|

CT and clinical assessment in asymptomatic and pre-symptomatic patients with early SARS-CoV-2 in outbreak settings

Abstract: Objectives The early infection dynamics of patients with SARS-CoV-2 are not well understood. We aimed to investigate and characterize associations between clinical, laboratory, and imaging features of asymptomatic and pre-symptomatic patients with SARS-CoV-2. Methods Seventy-four patients with RT-PCR-proven SARS-CoV-2 infection were asymptomatic at presentation. All were retrospectively identified from 825 patients with chest CT scans and positive RT-PCR following expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…In addition, one study aimed to investigate and distinguish between the clinical, imaging, and laboratory findings of COVID-19 cases. The researchers found that patients with CT infiltrate had higher KL-6 levels in comparison to patients with no CT infiltrates [ 29 ]. In another recent study, researchers measured KL-6 in COVID-19 patients during hospitalization and 6–9 months after being discharged from the hospital.…”
Section: Krebs Von Den Lungen-6 (Kl-6) In Covid-19 Patientsmentioning
confidence: 99%
“…In addition, one study aimed to investigate and distinguish between the clinical, imaging, and laboratory findings of COVID-19 cases. The researchers found that patients with CT infiltrate had higher KL-6 levels in comparison to patients with no CT infiltrates [ 29 ]. In another recent study, researchers measured KL-6 in COVID-19 patients during hospitalization and 6–9 months after being discharged from the hospital.…”
Section: Krebs Von Den Lungen-6 (Kl-6) In Covid-19 Patientsmentioning
confidence: 99%
“…Another issue is asymptomatic lesions in lungs in CT scan, which were detected in our first patients. This situation is reported in about 30% of asymptomatic SARS-CoV-2 positive patients (36).…”
Section: Discussionmentioning
confidence: 94%
“…[2020] (21) pointed out that diagnosis based on lung imaging is accurate. The CT imaging characteristics change with the disease condition, suggesting that CT images can be used for real-time diagnosis and evaluation (22).…”
Section: Discussionmentioning
confidence: 99%